Metalloregulatory proteins and nitric oxide signalling in bacteria. (19th November 2008) - Spiro, Stephen
Abstract : Bacterial gene regulators containing transition metal cofactors that function as binding sites for small ligands were first described in the 1990s. Since then, numerous metal-containing regulators have been discovered, and our knowledge of the diversity of proteins, their cofactors and the signals that they sense has greatly increased. The present article reviews recent developments, with a particular focus on bacterial sensors of nitric oxide.